VD_FINDINFO HC / 2013 / 500 vom 16. Juli 2013 - VD Tribunal cantonal (2013)
INDEMNITÉEN GÉNÉRAL, ASSISTANCE JUDICIAIRE | 122 al. 1 let. a CPC (CH), 2 al. 1 RAJ, 69 al. 3 TFJC (2010), 70 al. 3 TFJC (2010)